Visual Learning With Canva: Meningkatkan Literasi Digital Siswa Dengan Media Desain Interaktif di SMA 23 Makassar - Sulolipu, Andi Annisa; Rosmayanti, Vivit; Wahid, Areski; Ram, St. Wijdanah; Ishak, Suryadi (Yayasan Habiburrahman Jamalu Bina Ummat, 2025)
Digital literacy is an essential ability that students must have to face the challenges of the digital era. However, many students still use technology passively without developing creative and productive skills. The